Plan operativo anual en la Federación Deportiva de Los Ríos ubicado en la ciudad de Babahoyo, durante el periodo 2021. - Gavilánez Campbell, Nayeli Stephania (2023)
In every entity at the global level, whether public or private, it is important that efficient budget planning is carried out to properly manage the resources held by the organization from multiple sources. In the case of public sector entities, budget execution is important because it allows the creation of an operational plan that focuses on achieving the goals established by the institution. In a sports entity, the Annual Operating Plan (POA) focuses on ensuring compliance with accounting standards, improving processes, controlling costs, managing inventory and cash flow, and generating accurate financial reports, thus contributing to the success and sustainability of the sports entity. This case study is aimed at evaluating the budget execution for the determination of budget compliance in the Sports Federation of Los Ríos during the 2021 period through a review of the budget documents. This study was carried out through a descriptive research which allowed to identify the variable to be investigated, the types of research used is field and documentary. While the data collection techniques that are considered are interviews and documentary analysis. It was obtained as a result that the report of the budget of income and expenses of the Sports Federation of Los Ríos there are financial deviations. The main drawback of budget implementation is that the provisions of the annual operational plan are not always adjusted, a scenario that explains the inadequate implementation rate of certain accounts specified in the institutional budget.